2010
DOI: 10.5194/acp-10-719-2010
|View full text |Cite
|
Sign up to set email alerts
|

Bromoform and dibromomethane in the tropics: a 3-D model study of chemistry and transport

Abstract: Abstract.We have developed a detailed chemical scheme for the degradation of the short-lived source gases bromoform (CHBr 3 ) and dibromomethane (CH 2 Br 2 ) and implemented it in the TOMCAT/SLIMCAT three-dimensional (3-D) chemical transport model (CTM). The CTM has been used to predict the distribution of the two source gases (SGs) and 11 of their organic product gases (PGs). These first global calculations of the organic PGs show that their abundance is small. The longest lived organic PGs are CBr 2 O and CH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
174
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(190 citation statements)
references
References 32 publications
11
174
5
Order By: Relevance
“…In contrast, recent global emission estimates of the longer-lived CH 2 Br 2 (which has a lifetime of months, e.g. Warwick et al, 2006;Hossaini et al, 2010) have converged on a value of ∼ 60 Gg yr −1 (e.g. Liang et al, 2010;Ordóñez et al, 2012;Ziska et al, 2013).…”
Section: J Ashfold Et Al: Estimates Of Tropical Bromoform Emissimentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, recent global emission estimates of the longer-lived CH 2 Br 2 (which has a lifetime of months, e.g. Warwick et al, 2006;Hossaini et al, 2010) have converged on a value of ∼ 60 Gg yr −1 (e.g. Liang et al, 2010;Ordóñez et al, 2012;Ziska et al, 2013).…”
Section: J Ashfold Et Al: Estimates Of Tropical Bromoform Emissimentioning
confidence: 91%
“…We will refer to the full three-dimensional (longitudelatitude-time) grid of dilution values as the "dilution matrix". We approximate the effect of photochemical loss of CHBr 3 by allowing the mass associated with each trajectory to decay with an e-folding time of 15 days (similar to the expected lifetime of CHBr 3 in the tropical lower troposphere, Warwick et al, 2006;Hossaini et al, 2010;Liang et al, 2010). This has the effect of decreasing the dilution value in grid cells further from the measurement locations.…”
Section: Name Trajectory Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Is also justified, given that only the ratios of the lifetimes must be similar. Hossaini et al (2010) found altitude dependent ratios of the local tropical lifetimes for Ko et al (2003) for average tropospheric conditions at about 500 hPa altitude. This shows that the lifetime ratios vary mainly with altitude and less with latitude.…”
Section: Three-component Analysesmentioning
confidence: 99%
“…These values have been updated in the new WMO report to 24, 59 and 123 days for CHBr 3 , CHBr 2 Cl and CH 2 Br 2 (Montzka et al, 2011) the degradation rate especially of CH 2 Br 2 relative to CHBr 3 , as shown by Hossaini et al (2010), who calculated local lifetimes of 52 days for CH 2 Br 2 and 16 days for CHBr 3 in these regions. Using these values and an estimate of 29 days for the corresponding lifetime of CHBr 2 Cl, the slope of the chemical decay line is even lower (2.84).…”
Section: Three-component Analysesmentioning
confidence: 99%